PENGARUH KOORDINASI MATA TANGAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KETERAMPILAN SMASH BOLA VOLI - Shinta, Priti; Mukti, Ibrah Fastabiqi Bawana (YLPK Mahardhika, 2025)
This study aims to evaluate the impact of hand-eye coordination and leg muscle strength on smashing ability in volleyball games among UKM students. The method used is pre-experiment with one group pre-test and post-test design. The sample consisted of 16 female students taken using purposive sampling technique. The measuring instruments used in this study included smash accuracy test, wall toss test, and vertical jump test. The training program was carried out for six weeks with a frequency of three meetings a week. The average pretest score of 6.13 increased to 8.88 in the posttest (p = 0.009), indicating a significant increase in smashing skills. Cohen's d value of 0.90, which is included in the large effect category, is explained by the effect size study. These results indicate that improved smashing performance can be achieved through integrated training that builds leg muscle explosive power and eye-hand synchronization. The results of this study conclude that it is very important for student-level volleyball coaching programs to provide targeted activities for both areas. Various answers from the participants indicate that the training needs to be adjusted.